Advances in understanding physical and biological controls on eggs and larval distribution in Pacific fisheries: A review - Sumon, Md Afsar Ahmed; Hartono, Sugeng; Amran, Ramzi H.; Santanumurti, Muhammad Browijoyo; Khan, Saadullah Jan; Akther, Sajia; Gabr, Mohamed Hosny; Linh, Nguyen Vu; Doan, Hien Van (Universitas Malikussaleh, 2024)
The early stages of fish, comprising eggs and larvae, are exceptionally fragile and sensitive to environmental dynamics and climate change. Pacific Ocean (PO) currents play an important role in shaping the distribution of marine organisms, influencing global climate patterns, heat distribution, coastal temperatures, and nutrient redistribution. These currents reveal significant changes within the climate system. Their variability across different timescales can be attributed to the complex interplay of physical forces. These currents are subjected to diverse anthropogenic factors, exerting detrimental effects on the dispersal of fish larvae. Furthermore, climate change variables, including alterations in tropical PO temperature associated with the ENSO cycle, Atlantic Nino modes influencing equatorial Atlantic temperature, changes in ocean salinity, polar ice cap melting, increasing greenhouse gases, marine heatwaves, and fluctuations in subsurface flows, directly impact the distribution, abundance, and species composition of early life stages. Major Pacific fisheries, such as those targeting Pacific sardines, saury, and anchovies, undergo population booms and declines due to significant alterations in the current dynamics of currents and fronts within the PO. The anticipated intensification of the ENSO cycle, characterized by more frequent and severe El NiÃ±o (warm) and La NiÃ±a (cold) events as a result of climate change, is expected to significantly impact the early developmental stages of important commercial fish stocks regularly. This review synthesizes the current understanding of the physical and biological parameters driving changes in ocean currents and their implications for early fish dispersion, emphasizing the critical need for research in this area to inform global conservation efforts, fisheries management, and food security.